Application of the Importance Performance Analysis Method and Customer Satisfaction Index Methods to the Quality of Distance Learning Services for Students during the Covid 19 Pandemic - Sembiring, Carolina F; Anggraini, Nenny; Manulang, Ricky Martin (Advances in Social Sciences Research Journal, 2023)
This study discusses the analysis of satisfaction levels on distanced learning or PJJ of the student at Universitas Kristen Indonesia during the Covid-19 pandemic. The problem investigated are whether the expectation of UKI students meet service and its level of satisfaction. The research was carried out in the even semester of 2020/2021. The research method used is quantitative method with a survey approach through questionnaire distribution. Furthermore, the data were analyzed by the Importance Performance Analysis method (IPA) and Customer Satisfaction Index (CSI). IPA Matrix described the most meaningful attributes of students in the PJJ process, which is mapped in 4 quadrants of all variables that have impacts on quality PJJ services, and CSI are used to determine the overall student satisfaction level with the approach which considers the importance of the attributes measured during the Covid-19 pandemic. Based on the results of the analysis using IPA, it was known that the attributes which is the main priority in quadrant A are speed of access to the PJJ learning platform, fair assessment by the lecturer, the consistency in giving lectures well, reliability in managing class, use the PJJ platform, pay attention to the student, and understand the student’s difficulties during PJJ. For quadrant B, attributes that need to be maintained are the use of interactive tools for PJJ, easy access and connection of the PJJ platform, lecturers teaching in accordance to their field, lecturers answer student’s questions, lecturers master the material being taught, lecturers updating learning materials following the current conditions, encourages and motivates students to do the best learning in the PJJ process. Attribute on quadrant C, the low priority attribute are lecturers are able to adapt from conventional learning to PJJ, lecturers respond quickly and efficiently handle student needs and complaints, how lecturers answering student’s questions and comments, lecturers use variative learning platforms, lecturers put the long-term interest in their students to stay focus in PJJ. For quadrant D, an overrated attribute is the proactivity of lecturers in providing the information about PJJ to students. For CSI the attributes, the amount of learning carried out by UKI lecturers is 72.61%. It is still in the CSI range (between 0.66 - 0.80) which means that UKI students feel satisfied with the PJJ which was carried out during the Covid-19 pandemic.